Gestão de riscos e fatores contingenciais: um estudo na Universidade Federal da Paraíba - Fernandes, Thayná de Oliveira (2022)
The general objective of this study was to investigate the contingency factors that can affect risk management practices at the Federal University of Paraíba – UFPB. To do so, it was based on the Contingency Theory that seeks to understand how contingency factors can affect behavior and practices in organizations. Twenty people associated with the practice of risk management at UFPB were selected to participate in the research, as a research instrument, a questionnaire analyzed with descriptive statistics and Spearman correlation was used, while in the collection instrument of the semi-structured interview, it was analyzed with analysis content by Bardin (2011) and word clouds. The main results indicated that, in the perception of the research participants, the most consolidated practice of risk management is that servers and senior management demonstrate commitment to the fundamental values of UFPB. The results regarding the contingency factors that most affect risk management showed that in the external environment it is the regulation and control bodies, in the organizational structure it perceives interference of intellectual capital and physical structure, in terms of technology the most outstanding variable is data storage, in addition to the need for software with a purpose in risk management, in the contingency factor strategy it is noticed that it is essential to improve management processes and quality in the use of resources, in the contingency factor size there is a strong influence of budgetary resources and in the contingency factor culture, the need for greater organizational cooperation is identified. In the result presented on obstacles to the efficiency of risk management, the lack of training of servers was highlighted and, among the increase in risks due to bottlenecks, the misuse of public resources, increased operational and legal risk was evidenced. Therefore, this research contributed to identify the contingency factors and obstacles that impede the improvement of risk management at UFPB, suggesting improvements to the studied institution and helping other federal Public Education Institutions (HEIs) to investigate the challenges to maintain adequate risk management.